Brotherhood of the wolf [videorecording (DVD)] - Gans, Christophe, 1960-; Le Bihan, Samuel; Cassel, Vincent, 1966-; Dequenne, Émilie; Bellucci, Monica, 1968- (Universal Studios, 2002)
When a mysterious beast ravages the countryside, two men are called in to fight the evil and end the reign of terror. The only way they can save the land from the unspeakable fright is to unearth a dark power, reveal a deadly secret and face their greatest fears.